Conserved Insulin Signaling in the Regulation of Oocyte Growth, Development, and Maturation - DAS, DEBABRATA (Mol Reprod Dev, 2017)
Insulin signaling regulates various aspects of physiology, such as glucose homeostasis and aging, and is a key determinant of female reproduction in metazoans. That insulin signaling is crucial for female reproductive health is clear from clinical data linking hyperinsulinemic and hypoinsulinemic condition with certain types of ovarian dysfunction, such as altered steroidogenesis, polycystic ovary syndrome, and infertility. Thus, understanding the signaling mechanisms that underlie the control of insulin-mediated ovarian development is important for the accurate diagnosis of and intervention for female infertility. Studies of invertebrate and vertebrate model systems have revealed the molecular determinants that transduce insulin signaling as well as which biological processes are regulated by the insulin-signaling pathway. The molecular determinants of the insulin-signaling pathway, from the insulin receptor to its downstream signaling components, are structurally and functionally conserved across evolution, from worms to mammals – yet, physiological differences in signaling still exist. Insulin signaling acts cooperatively with gonadotropins in mammals and lower vertebrates to mediate various aspects of ovarian development, mainly owing to evolution of the endocrine system in vertebrates. In contrast, insulin signaling in Drosophila and Caenorhabditis elegans directly regulates oocyte growth and maturation. In this review, we compare and contrast insulin-mediated regulation of ovarian functions in mammals, lower vertebrates, C. elegans, and Drosophila, and highlight conserved signaling pathways and regulatory mechanisms in general while illustrating insulin’s unique role in specific reproductive processes.